Multi-Scalar Trade Unionism: Lessons from Maritime Unions - Fairbrother, Peter; Gekara, Victor (Relations industrielles / Industrial Relations, 2016)
Union approaches in relation to the global recalibration of work and employment relations and practices over the last three decades are being worked out in practice. The question for unions is by which means they either have leverage or the potential to exercise power in relation to state and corporate decisions and strategies. Unions thus face challenging questions about the ways they organize, exercise their capacities and attempt to meet their purposes. With reference to the Australian maritime sector, the study examines the ways the main union, the Maritime Union of Australia, developed multi-scalar approaches to localized events. The problem unions face is to defend and advance workers’ interests. The task is to organize, to realize their capacities to defend and advance maritime workers’ interests, increasingly in multi-scalar ways.The argument is that leaderships and activity that ‘bridge’ scalar relationships are an important condition in this process. There appears to be a complex set of cross-connections between the local, the national and the international. While transnational connectivity increasingly defines contemporary forms of trade unionism, these scalar relations are defined in relation to the workplace, the everyday world, and by the ways that transport is a defining characteristic of the global world. These relations constitute contemporary class struggle where work and employment relations are always in a process of change and development. Trade unionism, thus, remains a collective expression of power relations, in an increasingly internationalized world of work and employment.Thus, this research presents important lessons for multi-scalar organization and campaigning by unions to realize their capacities and purpose. Nonetheless, this study is only a beginning. While it indicates the processes of bridging, the next step is to investigate the variety of ways that bridging may take place and with what outcomes for the development of multi-scalar activity.